Illustrator 10 - Chong, Sae Nan (Muska & Lipman Pub., 2002)
If you're a professional designer looking to learn advanced techniques and applications of Adobe Illustrator 10, then you'll want "Illustrator 10: Mastering Artistic Design." Through stunning full-color examples and step-by-step explanation in 13 projects, you'll learn how to use new and original features to improve the artistic design process. All original artwork and source files are included on an accompanying CD-ROM